Aristotle's Rhetoric in the East : the Syriac and Arabic translation and commentary tradition - Vagelpohl, Uwe. (Islamic Philosophy, Theology and Science. Texts and Studies, 2008)
The two centuries following the rise of the Abbasid caliphate in 750 witnessed a wave of translations from Greek into Syriac and Arabic. The translation and reception of Aristotle's Rhetoric is a prime example for the resulting transformation of antique learning in the Islamic world and beyond. On the basis of a close textual analysis of the Rhetoric, this study develops elements of a comparative "translation grammar" of Greek-Arabic translations. Contextualizing the analysis with an account of the textual history and the Syriac and Arabic philosophical tradition drawing on the Rhetoric , it throws new light on the inner workings of the "translation movement" and its impact on Islamic culture.